Analysis of Conversational Structure in “Cerita Untungs” Podcast - Siti Syarifatul Jannah; Norma Ita Sholichah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
Abstract Podcasts are digital media where speakers communicate naturally, making them suitable for analyzing conversational structure. Although many studies explore conversations in classrooms, talk shows, and daily interactions, research focusing on Indonesian podcast, especially those discussing educational issues is still limited. Therefore, this study aims to identify and explain the five conversational elements proposed by Yule (2006): turn-taking, pauses, overlaps, back-channels, and adjacency pairs. The data were collected from a 36 minute episode of the Cerita Untungs podcast titled Kurikulum Pendidikan Indonesia Bikin Bodoh, Pak Nadiem Menteri Gagal, SMP Belum Bisa Baca?, which was transcribed and coded using a descriptive qualitative method. The results show 435 instances of turn-taking, 141 instances of pauses, 93 occurrences of overlaps, 153 back-channel responses, and 129 adjacency pairs. These features help organize the flow of the conversation and support the speakers in delivering their ideas clearly. The findings also indicate that the conversational patterns are influenced by the podcast’s informal communication style and its discussion of issues related to Indonesia’s education system. This study contributes to understanding conversational structure in digital media and highlights the role of Indonesian podcasts as platforms for public discussion on social and educational issues.